If (gx) = 2x^2 -3x, evaluate, expand and simplify completely.

g(-2)

g(-c)

g(d^2)

g(-2)

Printable View

- Mar 5th 2006, 12:33 PMbatman123Simplify
If (gx) = 2x^2 -3x, evaluate, expand and simplify completely.

g(-2)

g(-c)

g(d^2)

g(-2) - Mar 5th 2006, 01:50 PMJamesonQuote:

Originally Posted by**batman123**

g(-2) is just plugging in -2 for x. So we get g(-2)=4-3(-2)=16

g(-c) is the same thing. Plug in -c for x, and see what you get. - Mar 5th 2006, 08:29 PMearbothQuote:

Originally Posted by**batman123**

first: The last problem is the same as the first problem, so I'll not do that again.

second: Plug in the given value for x and calculate:

$\displaystyle g(-2)=2 \cdot (-2)^2-3 \cdot (-2)=2 \cdot (4)+6=14$

$\displaystyle g(-c)=2 \cdot (-c)^2-3 \cdot (-c)=2 \cdot c^2+3c$

$\displaystyle g(d^2)=2 \cdot (d^2)^2-3 \cdot (d^2)=2 \cdot (d^4)-3d^2$

Greetings

EB